The effects of EFB compost and Hexaconazole on Beta-Carotene content and its relationship with the yield components of sweet potato Var. Vitato / Borhan Abdul Haya [et. al]... - Abdul Haya @ Yahya, Borhan; Abdullah, Mohd Yusoff; Tajarudin, Nur Kharunisa; Muhamad Basha, Nur Azwa (Universiti Teknologi MARA, Negeri Sembilan, 2017)
Field experiment was conducted on sandy tin-tailing soil to test the effectiveness of oil palm EFB compostand hexaconazole (HEX) growth regulator in increasing the storage root β-carotene content and yield components of sweet potato var. VitAto. The treatment plants were arranged using the RCBD replicated four times. The treatments used were the recommended rate of inorganic fertilizer practice in VitAto cultivation (control), EFB compost (F-EFB) and the combination of EFB compost with 10 ppm (F- EFB+10 ppm) and 30 ppm HEX (F-EFB+30 ppm). As results, F-EFB+30 ppm HEX treatment was the best in increasing the storage root β-carotene content up to 6052 µg/100 g, 15% significantly higher than control at the maturity stage. At similar growth stage, this treatment also increased the storage root total fresh weight, dry mass production and number by 35, 17 and 125% significantly higher than control respectively. The β-carotene content showed high correlation with these parameters (r = 0.56***, 0.67*** and 0.53*** respectively) through correlation studies. In conclusion, F-EFB+30 ppm HEX was the best treatment applied with respect to the enhancement of storage root β-carotene content and yield components. It is proposed that this combination treatment could be used by farmers as an alternative practice to the inorganic fertilizer application in VitAto cultivation on sandy soil.